2021
DOI: 10.1055/a-1510-8896
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic-Metabolite-Based Intermittent Fasting Enables a Sustained Reduction in Insulin Resistance in Type 2 Diabetes and Metabolic Syndrome

Abstract: Insulin resistance is the hallmark of Type 2 Diabetes and is still an unmet medical need. Insulin resistance lies at the crossroads of non-alcoholic fatty liver disease, obesity, weight loss and exercise resistance, heart disease, stroke, depression, and brain health. Insulin resistance is purely nutrition related, with a typical molecular disease food intake pattern. The insulin resistant state is accessible by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…In all of these, a significant reduction was obtained after the diet, finding the highest difference, for both men and women, with the METS-IR. Different previous studies found an improvement in the TyG index with diet [91,92], as shown in our analysis. In a previous cross-sectional study conducted by our research group, we found an association between people following a Mediterranean diet and a lower index of insulin resistance measured with METS-IR [54].…”
Section: Discussionsupporting
confidence: 86%
“…In all of these, a significant reduction was obtained after the diet, finding the highest difference, for both men and women, with the METS-IR. Different previous studies found an improvement in the TyG index with diet [91,92], as shown in our analysis. In a previous cross-sectional study conducted by our research group, we found an association between people following a Mediterranean diet and a lower index of insulin resistance measured with METS-IR [54].…”
Section: Discussionsupporting
confidence: 86%
“…Elevated blood triglycerides accompanied by lower HDL levels represent an insulin-resistant metabolic status and are purely dietrelated. According to Rohner et al (2021), the macromolecular dietary pattern of patients with insulin resistance, prediabetes, or type 2 diabetes shows a similar pathological baseline dietary pattern, independent of BMI. This is characterized by a significant excess intake of saturated fats and glucose and a too low intake of fiber, polyphenols, magnesium, potassium, and vitamin D [Rohner et al 2021].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Reversal of insulin resistance to a normal response can effectively be achieved through an everyday diet purposed to de-escalate inflammation and rewire the metabolic and signaling landscape by sustained epigenetic remodeling [Rohner et al 2021]. The treatment is a precise personalized molecular nutrition strategy with intermittent fasting enriched with selected nutritional cofactors.…”
Section: Facile Detection Successful Prevention and Effective Treatme...mentioning
confidence: 99%
“…Existe un notorio descenso de la insulina en la tarde, por lo que las cenas tardías incrementan el riesgo de diabetes y otros componentes del SM (14), se evidenció que la ingesta de alimentos en altas horas de la noche aumentan el riesgo cardiovascular y a su vez esta desregulación del ritmo favorece a la insulinorresistencia, a diferencia de quienes se alimentan solo hasta la mitad del día que revelan un mejor control de lípidos, glucosa e inflamación (7). Por otra parte, la resistencia a la insulina contribuye potencialmente al incremento del Índice de Masa Corporal (IMC) (16). La ultima teoría, hace referencia al estado cetogénico, que al promover a este cambio metabólico intermitente causa el ascenso de las concentraciones de B-hidroxibutirato y el surgimiento de cetonas al cabo de 6 a 8 horas de ayuno.…”
Section: Resultsunclassified
“…Los efectos metabólicos con mayor evidencia científica son cuatro, que incluye pérdida de peso, disminución de las concentraciones séricas de insulinaglucosa, TG, y en algunas ocasiones modificaciones que beneficien la PA (3,7,(16)(17)(18).…”
Section: Resultsunclassified